Application Of The Dynamic Vibration Absorber To Reduce The Noise And Vibration Of The Automotive Hvac System - Aziz, Muhammad Safwan Abdul (Universiti Sains Malaysia, 2019)
The purpose of this project is to study the effect of Dynamic Vibration Absorber (DVA) to reduce the humming type noise and vibration of the Proton Exora. The DVA was designed and tuned according to the natural frequency of the AC Pipe structure and applied to the system and vehicle level of the Proton Exora HVAC sytem. The humming type noise and vibration characteristics of the HVAC components were recorded and compared before and after the implementation of DVA. The implementation of DVA was found to improve the vibration level of the AC Pipe by 80% and subsequently improving the noise and vibration level of the whole HVAC system by 1.5 dB. It has been observed that the DVA has an effective frequency range of 100 – 500 Hz for the vehicle level and 75-250 Hz for the system level.